Impact of inverter controller-based grid-connected pv system in the power quality - Al-Shetwi, Ali Q.; Muhamad Zahim, Sujod; M. A., Hannan; Abdullahd, Majid A.; Al-Ogaili, Ali Saadon; Ker, Pin Jern (Warsaw University of Technology, 2020)
In a Grid-Connected Photovoltaic System (GCPS), the inverters are applied for integration with the power grid. This integration brings some issues at the connection point. Therefore, grid-tied inverter control performs a vital role in feeding the power system with good power quality. This study presents a current-controlled Voltage Source Inverter (VSI) strategy for large-scale GCPS generates 1000 kW rated of power. The methodology and structure of the control system are presented. The power quality issues such as harmonics, voltage fluctuation, voltage unbalance, and power factor are limited at the interfacing point into the required limits as imposed by the standards. This study also discusses the controller design and the simulation results are introduced to show its effectiveness. Furthermore, the values obtained may be used to evaluate the power supply quality of various inverter controllers.